High fidelity quantum gates of trapped ions in the presence of motional heating - Farhang Haddadfarshi; Florian Mintert (New Journal of Physics, 2016)
We describe entangling quantum gates for trapped ions mediated by a dissipative bus mode and show that suitably designed, polychromatic control pulses decrease ion-phonon entanglement substantially while maintaining the mediated interaction. In particular for multi-qubit gates this yields a significant improvement in gate performance.